(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2019)
Tara Atluri’s book, Uncommitted Crimes: The Defiance of the Artistic Imagi/nation, is a celebration of those who are reimagining Canadian narratives of multiculturalism, diversity, and equity. Colonial, cisgendered, heteronormative, and racist narratives that may yet be invisible to the inhabitants of Turtle Island are revealed through Atluri’s depiction of a diverse selection of artists and art.